Zwitterionic amino acid-based Poly(ester urea)s suppress adhesion formation in a rat intra-abdominal cecal abrasion model. (November 2019) - Dreger, Nathan Z.; Zander, Zachary K.; Hsu, Yen-Hao; Luong, Derek; Chen, Peiru; Le, Nancy; Parsell, Trenton; Søndergaard, Clause; Dunbar, Misha L.; Koewler, Nathan J.; Suckow, Mark A.; Becker, Matthew L.
Abstract: Hernia repair outcomes have improved with more robust material options for surgeons and optimized surgical techniques. However, ventral hernia repairs remain challenging with an inherent risk of post-surgical adhesions in the peritoneal space which can occur regardless of interventional material or its surgical placement. Herein, amino acid-based poly(ester urea)s (PEUs) with varied amount of an allyl ether side chains were modified post polymerization modification with the zwitterionic sulfnate group (3-((3-((3-mercaptopropanoyl)oxy)propyl) dimethylammonio)propane-1-sulfonate) to promote anti-adhesive properties. These alloc-PEUs were processed using roll-to-roll fabrication methods to afford films that were amenable to surface functionalization via a zwitterion-thiol. Functional group availability on the surface was confirmed via fluorescence microscopy, x-ray photoelectron spectroscopy (XPS), and quartz crystal microbalance (QCM) measurements. Zwitterionic treated PEUs exhibited reduced fibrinogen adsorption in vitro when compared to unfunctionalized control polymer. A rat intrabdominal cecal abrasion adhesion model was used to assess the extent and tenacity of adhesion formation in the presence of the PEUs. The 10% alloc-PEU zwitterion functionalized material was found to reduce the extent and tenacity of adhesions when compared to adhesion controls and the unfunctionalized PEU controls.